If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6 + x = 90 Reorder the terms: 6 + 5x + x = 90 Combine like terms: 5x + x = 6x 6 + 6x = 90 Solving 6 + 6x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 90 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 90 + -6 6x = 90 + -6 Combine like terms: 90 + -6 = 84 6x = 84 Divide each side by '6'. x = 14 Simplifying x = 14
| 175=5(x-50)+50 | | 7x+1=15x+33 | | 75=(10+2x)(5+2x) | | -x/5=20 | | -8(x-5)=-5x+10 | | 1.3+2.5=6.4 | | 3(2x-14)+x= | | -38.48=-5.2 | | 6-1/t-5/t^2=0 | | (7a-2b+19)+(13a+5b-12)= | | 4j=24 | | 4+2(m+8)= | | x^2-10v+25=0 | | 13x-13=12x-4 | | 3(x-4)=-6x+6 | | -39+x+2x=36 | | 5x=180-(5x-30) | | 4n-3=2 | | 3.5-0.25= | | 36x=12x | | 3*ln*(2x-1)+4=19 | | 12Y=3Y-8(5) | | 5(3x-1)=5 | | 5(x+3)+12=-4x(-2+3) | | 5x-12-3x=7x-2-x | | 20-(15-20s)8=6 | | (8+z)(4z+6)=0 | | -4n+16=-8n-32 | | C*-13=663 | | 3(2x-14)+x=15 | | -15+3x=39 | | 2x-y=4andx-4y |